Mutu Radiograf Panoramik Digital Ditinjau dari Segi Artefak pada Rumah Sakit di Kota Semarang, Indonesia - Mohammad Yusuf; Shella I. Novianti; Abu Bakar; Vivi A. Noor (Universitas Sam Ratulangi, 2023)
Abstract: A panoramic radiograph can be classified as a good image (acceptable) for diagnosis examination if it has good quality image including no artefacts. The shape and size of artefact will affect the accuracy of diagnosis in a disease or disorder. This study aimed to determine the quality of digital panoramic radiographs in terms of artefacts at hospitals in the city of Semarang. This was a descriptive and observational study. This study was conducted at three Radiology Installations of Semarang Hospital, namely Sultan Agung Islamic Hospital, Tugurejo Hospital, and Dr. Karyadi Hospital. Patients’ identities were not disclosed to protect the privacy of the patient. The population consisted of 1305 radiographs, and 77 radiographs were taken for each installation in DICOM/JPEG format and adjusted to the check list. Observations were made by interobserver and analyzed using descriptive statistical analysis. The results showed that there were artefacts in the form of small spots (ɵ<10mm) that did not interfere with the diagnosis by 25.2%, spots with small size (<10mm) and interfered with the diagnosis by 0.65%, small size earrings that did not interfere with the diagnosis by 0.33%. In conclusion, artefacts on digital panoramic radiographs at Semarang City Hospital were as many as 26.1%. It is expected that all hospitals will be able to evaluate the quality of the radiographic results, especially in terms of artefacts, to increase the accuracy of diagnosis. Keywords: artefact; panoramic radiography; digital radiography; image quality Abstrak: Sebuah radiograf panoramik dikatakan dapat diterima sebagai gambar yang baik (acceptable) untuk diagnosis bila mempunyai kualitas yang baik di antaranya tidak terdapat artefak. Bentuk dan ukuran artefak akan memengaruhi ketepatan diagnosis penyakit atau kelainan. Penelitian ini bertujuan untuk mengetahui kualitas radiograf panoramik digital ditinjau dari segi artefak pada Rumah Sakit di Kota Semarang. Jenis penelitian ialah deskriptif observasi. Sampel diambil dari tiga Instalasi Radiografi Rumah Sakit Semarang yaitu Rumah Sakit Islam Sultan Agung, RSUD Tugurejo, Rumah Sakit Umum Pusat dr. Kariyadi. Identitas pasien tidak disebutkan untuk menjaga privasi dari pasien. Populasi terdiri dari 1305 radiograf dan diambil 77 radiograf setiap intalasi dengan format DICOM/JPEG dan disesuaikan dengan check list. Pengamatan dilakukan oleh peneliti, training antar teman, spesialis radiologi dan dianalisis dengan analisis statistik deskriptif. Hasil penelitian mendapatkan adanya artefak berupa bercak dengan ukuran kecil (ɵ<10mm) dan tidak mengganggu diagnosis sebesar 25,2%, bercak dengan ukuran kecil (<10mm) dan mengganggu diagnosis sebesar 0,65%, dan pasien menggunakan anting ukuran kecil dan tidak mengganggu diagnosis sebesar 0,33%. Simpulan penelitian ini ialah terdapat artefak pada radiograf panoramik digital di Rumah Sakit Kota Semarang sebesar 26,1%. Diharapkan semua rumah sakit melakukan evaluasi mutu hasil radiograf terutama dari segi artefak untuk meningkatkan ketepatan diagnosis. Kata kunci: radiograf panoramik; panoramik digital; kualitas gambar; artefak